2017
DOI: 10.1186/s12872-017-0640-0
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary syndrome and acute kidney injury: role of inflammation in worsening renal function

Abstract: BackgroundAcute Kidney Injury (AKI), a common complication of acute coronary syndromes (ACS), is associated with higher mortality and longer hospital stays. The role of cytokines and other mediators is unknown in AKI induced by an ACS (ACS-AKI), leading to several unanswered questions. The worsening of renal function is usually seen as a dichotomous phenomenon instead of a dynamic change, so evaluating changes of the renal function in time may provide valuable information in the ACS-AKI setting. The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 58 publications
1
26
0
Order By: Relevance
“…In our STEMI patients, reduced EF was associated with Killip class ≥II, especially in the subset of patients who developed AKI. Clinical studies including STEMI patients showed that high NT-proBNP, associated with hypotension, hyponatremia, venous congestion and cardiorenal syndrome, is a risk factor for AKI [9,22,23]. AHF leads to reduced renal blood flow which activates the sympathetic and renin-angiotensin-aldosterone systems and induces ventricular remodeling [24].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our STEMI patients, reduced EF was associated with Killip class ≥II, especially in the subset of patients who developed AKI. Clinical studies including STEMI patients showed that high NT-proBNP, associated with hypotension, hyponatremia, venous congestion and cardiorenal syndrome, is a risk factor for AKI [9,22,23]. AHF leads to reduced renal blood flow which activates the sympathetic and renin-angiotensin-aldosterone systems and induces ventricular remodeling [24].…”
Section: Discussionmentioning
confidence: 99%
“…Increased inflammatory markers, such as white blood cell (WBC)/leukocyte count and CRP, in STEMI patients may be due to infection or, more often, due to recruitment of leukocytes to the site of injury in the myocardium [9]. Infiltrating leukocytes are the source of inflammatory cytokines such FIGURE 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations